2017
DOI: 10.1162/jocn_a_01028
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Structure Predicts Statistical Learning and Associative Inference Abilities during Development

Abstract: Despite the importance of learning and remembering across the lifespan, little is known about how the episodic memory system develops to support the extraction of associative structure from the environment. Here, we relate individual differences in volumes along the hippocampal long axis to performance on statistical learning and associative inference tasks—both of which require encoding associations that span multiple episodes—in a developmental sample ranging from ages 6–30 years. Relating age to volume, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
208
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(252 citation statements)
references
References 78 publications
(106 reference statements)
23
208
4
Order By: Relevance
“…Investigating subfield contributions along the full anatomical extent of HC could therefore refine our understanding of how HC subfield and memory development are related (see ref. 29; however, this study also highlights the controversies regarding methods for identifying HC subfield in the head and tail, see ref. 49).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Investigating subfield contributions along the full anatomical extent of HC could therefore refine our understanding of how HC subfield and memory development are related (see ref. 29; however, this study also highlights the controversies regarding methods for identifying HC subfield in the head and tail, see ref. 49).…”
Section: Discussionmentioning
confidence: 62%
“…The inclusion of the latter measures was exploratory and served the purpose of probing the specificity of a potential association between pattern separation/completion and HC subfield maturation. For instance, previous studies reported age-related differences in functional and structural HC contributions to source memory (27,28) and associative inference (29) along the longitudinal HC axis. However, the relationship between age differences in source memory and HC subfield development remains elusive.…”
mentioning
confidence: 99%
“…Performance of healthy participants in within-group studies is often compared to chance (e.g., Schlichting, Guarino, Schapiro, Turk-Browne, & Preston, 2017; Arciuli et al, 2014; Toro, Sinnett, & Soto-Faraco, 2005; Creel et al, 2004; Saffran, Johnson, Aslin, & Newport, 1999). Comparing performance to chance levels is also a common metric of learning and memory in the amnesia literature (e.g., Dede, Frascino, Wixted, & Squire, 2016; Schapiro et al, 2014; Hannula et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has suggested that the AHc undergoes substantial development throughout the school years (Ghetti and Bunge, 2012). Anatomically, Gogtay et al (2006) showed that AHc volume decreases between 4 and 25 years of age, and this structural change has been recently linked to children's increasing propensity for binding elements across multiple learning episodes (Schlichting et al, 2016). Functionally, Ghetti et al (2010) observed age-related increases in AHc engagement during memory encoding.…”
mentioning
confidence: 99%
“…Functionally, Ghetti et al (2010) observed age-related increases in AHc engagement during memory encoding. These concurrent decreases in anatomical volume and increases in functional activity may be best conceptualized as a fine-tuning of AHc learning mechanisms throughout development (Schlichting et al, 2016). Understanding how such changes affect the automaticity with which children access schematic knowledge will have important implications for memory theories and educational practice.…”
mentioning
confidence: 99%